Predictors and Outcomes of Employee Engagement: Empirical Study of Nepali Employees - Chhetri, Sabina Baniya (Journal of Business and Management Research, 2017)
Engaged employees are the most sought-after resources in organizations across the globe. Efforts have been made by academicians and management consultants to help organizations understand the dynamics of Employee Engagement. Little is known, though, about Employee Engagement and its predictors and outcomes in the context of Nepali organizations. This study examined the relationship between predictors and outcomes of Employee Engagement among employees of Nepali organizations and tested its mediating effects. The study was conducted among 158 employees working in various organizations. Correlation, multiple regression, and bootstrapping methods were used to test the hypothesized relationships. The results in general found support for all the hypothesized relationships between predictor variables, viz.: Person-Organization Fit (P-O), Perceived Organizational Support (POS), and Employee Engagement. Likewise, Employee Engagement and outcome variables: Job satisfaction, Organizational Citizenship Behavior (OCB) and Counterproductive Work Behavior (CWB) were related too. Employee Engagement fully mediated the relationship between P-O Fit and OCB, POS and OCB, and POS and CWB while partially mediated the relationship between P-O Fit and Job satisfaction, P-O Fit and CWB and POS and Job satisfaction. The findings are discussed and implications identified.